2019
DOI: 10.1002/ijgo.12967
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum psychoactive substance abuse after severe maternal morbidity

Abstract: Objective To evaluate drug use among mothers during the postpartum period after a severe pregnancy‐related complication. Methods A retrospective cohort study of maternal morbidity including maternal near‐miss and control groups conducted in a tertiary hospital in Campinas, Brazil, between July 2008 and June 2012. The Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) was used to assess drug use during lifetime, pregnancy, and in the previous 3 months. Results Of 638 women evaluated, drug use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although the country of origin differed greatly between the studies, the majority were set in Africa (n = 8) [10][11][12][15][16][17]22,23 and South America (n = 5). 9,13,[18][19][20] One study was set in Europe (Sweden) 21 and one in Asia (India) 14 (Table 1). A total of 31 558 women were enrolled in the studies.…”
Section: Re Sultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the country of origin differed greatly between the studies, the majority were set in Africa (n = 8) [10][11][12][15][16][17]22,23 and South America (n = 5). 9,13,[18][19][20] One study was set in Europe (Sweden) 21 and one in Asia (India) 14 (Table 1). A total of 31 558 women were enrolled in the studies.…”
Section: Re Sultsmentioning
confidence: 99%
“…10,12,16,17,22 The remaining seven studies reported age as an interval between ≤19 and ≥40. 9,13,15,[18][19][20][21] Time to follow-up ranged from 5 months to 5 years.…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations